Factor Structure of Subjective Responses to Alcohol in Light and Heavy Drinkers. (22nd May 2015) - Bujarski, Spencer; Hutchison, Kent E.; Roche, Daniel J. O.; Ray, Lara A.
<x xml:space="preserve">Abstract</x> Background Subjective responses (SRs) to alcohol have been implicated in alcoholism etiology, yet less is known about the latent factor structure of alcohol responses. The aim of this study was to examine the factor structure of SR using a battery of self‐report measures during a controlled alcohol challenge. Methods Nontreatment seeking drinkers (N = 242) completed an intravenous alcohol challenge including the following SR measures: Biphasic Alcohol Effects Scale, Subjective High Assessment Scale, Profile of Mood States, Alcohol Urge Questionnaire, and single items assessing alcohol "Liking" and "Wanting." Ascending limb target breath alcohol concentrations were 0.02, 0.04, and 0.06, and descending limb target was 0.04 g/dl. Exploratory factor analyses were conducted separately on estimates of mean and dose responses on the ascending limb and on descending limb data. To examine the generalizability of this factor structure, these analyses were repeated in heavy drinkers (≥14 drinks/wk for men, ≥7 for women; n = 132) and light drinkers (i.e., nonheavy drinkers; n = 110). Results In the full sample, a 4‐factor solution was supported for ascending limb mean and dose responses and descending limb data representing the following SR domains: Stimulation/Hedonia, Craving/Motivation, Sedation/Motor Intoxication, and Negative Affect. This 4‐factor solution was replicated in heavy drinkers. In light drinkers, however, SR was better summarized by a 3‐factor solution where ascending mean and descending limb responses consisted of Stimulation/Hedonia, Craving/Motivation, and a general negative valence factor, and dose responses consisted of a general positive valence factor, Sedation/Motor Intoxication, and Negative Affect. Conclusions These findings suggest that SR represents a multifaceted construct with consistent factor structure across both ascending and descending limbs. Further, as drinking levels escalate, more defined Craving/Motivation and negative valence dimensions may emerge. Longitudinal studies examining these constructs are needed to further our understanding of SR as potentially sensitive to alcohol‐induced neuroadaptation.